Eosinophils and Chronic Respiratory Diseases in Hospitalized COVID-19 Patients - Valverde-Monge, Marcela; Cañas, José A.; Barroso, Blanca; Betancor, Diana; Ortega-Martin, Laura; Gómez-López, Alicia; Rodríguez-Nieto, María Jesús; Mahíllo-Fernández, Ignacio; Sastre, Joaquín; Del Pozo, Victoria (Frontiers in Immunology, 2021)
Background: Studies on the role of eosinophils in coronavirus disease 2019 (COVID-19) are scarce, though available findings suggest a possible implication in disease severity. Here, we analyzed the relationship of eosinophils and COVID-19 addressing the association with the severity of disease, especially between different respiratory diseases. Methods: We performed a retrospective analysis of 3018 subjects who were attended at either of two public hospitals in Madrid (Spain) with PCR-confirmed to coronavirus (SARS-CoV-2) infection from January 31 to April 17, 2020. Patients with eosinophil counts below 0.02×109/L were considered to have eosinopenia. Individuals with respiratory diseases (n=384) were classified according to their particular disease, i.e. asthma, chronic pulmonary obstructive disease, or obstructive sleep apnea. Results: Among the 3018 patients enrolled, 479 were excluded because lack of enough information at the time of admission. Of 2539 subjects assessed, 1396 patients had an eosinophil count performed on admission, revealing eosinopenia in 376 (26.93%). Eosinopenia on admission was associated with a higher risk of intensive care unit (ICU) or respiratory intensive care unit (RICU) admission (OR:2.21; 95%CI:1.42-3.45; p<0.001) but no increased risk of mortality (p>0.05). Conclusions: Eosinopenia on admission conferred a higher risk of severe disease, requiring ICU/RICU care but was not associated with increased mortality. Moreover, patients with chronic respiratory diseases who develop COVID-19, age seems to be the main risk factor for a higher risk of progressing to severe disease requiring ICU/RICU admission or death.